Nickel/Brønsted Acid-Catalyzed Chemo- and Enantioselective Intermolecular Hydroamination of Conjugated Dienes - Long, Jiao (iScience, 2019)
A novel nickel/Brønsted acid-catalyzed asymmetric hydroamination of acyclic 1,3-dienes has been established. A wide array of primary and secondary amines can be transformed into allylic amines with high yields and high enantioselectivities under very mild conditions. Moreover, our method is compatible with various functional groups and heterocycles, allowing for late-stage functionalization of biologically active complex molecules. Remarkably, this protocol exhibits good chemoselectivity with respect to amines bearing two different nucleophilic sites. Mechanistic studies reveal that the enantioselective carbon-nitrogen bond-forming step is reversible.